2016
DOI: 10.1007/s00586-016-4740-9
|View full text |Cite
|
Sign up to set email alerts
|

The changes of syrinx volume after posterior reduction and fixation of basilar invagination and atlantoaxial dislocation with syringomyelia

Abstract: Posterior reduction and fixation of the AAD and BI can effectively enlarge the foramen magnum, improve the cerebrospinal fluid circulation and consequently reduce the volume of the syrinx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Widely used surgical treatments aim to relieve the pressure on the medulla and cervical spinal cord and maintain or reconstruct atlantoaxial stability [ 3 , 5 ]. In 2004, Goel [ 6 ] reported that implanting a lateral joint fusion cage achieved good results in treating BI-AAD.…”
Section: Introductionmentioning
confidence: 99%
“…Widely used surgical treatments aim to relieve the pressure on the medulla and cervical spinal cord and maintain or reconstruct atlantoaxial stability [ 3 , 5 ]. In 2004, Goel [ 6 ] reported that implanting a lateral joint fusion cage achieved good results in treating BI-AAD.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for postoperative improvement should thus be attributed in large part to the reduction, which indirectly decompresses the brain stem by a protruding odontoid, and partially in the stabilization, which serves to sustain this effect. This hypothesis was proposed by other authors [71,83,92]. Wang et al analyzed the reduction of syrinx volume and CVJ alignment in 71 patients treated with OCF and bony suboccipital decompression after reduction.…”
Section: Basilar Invagination-discussion Of Evidencementioning
confidence: 85%
“…Wang et al analyzed the reduction of syrinx volume and CVJ alignment in 71 patients treated with OCF and bony suboccipital decompression after reduction. They found that for 93.0% of patients with satisfying reposition of the odontoid, a syrinx regression was achieved as well [92]. In a recent study, Salunke and colleagues reduced and fused 38 patients with CM and BI, of which 91.9% maintained both clinical and radiographical improvement after 6 months [83].…”
Section: Basilar Invagination-discussion Of Evidencementioning
confidence: 96%
See 1 more Smart Citation
“…Chiari malformations (CM), associated with a reduced volume of the posterior fossa, are typically treated with foramen magnum decompression (FMD) (i.e., to enlarge the posterior fossa volume). [4,9,10] When CM are combined with atlantoaxial dislocation (AAD) and basilar invagination (BI), the posterior fossa volume is even further reduced; the instability requires C1–C2 distraction, realignment, and arthrodesis. [1,5-7,10] The fixation per se is likely to relieve anterior cervicomedullary compression and increase the overall posterior fossa volume.…”
Section: Introductionmentioning
confidence: 99%